Schön und schuldig: kulturgeschichtliche und philologische Betrachtungen zum Körper der Maria Magdalena in ihrer spätmittelalterlichen Bekehrungslegende ; mit einer Neuerfassung des Überlieferungszusammenhangs - Kirakosian, Racha; Möllenbrink, Linus (Poetica, 2025)
Abstract This article analyses the portrayal of Mary Magdalene’s body in a late medieval conversion legend and its vernacular adaptations, drawing on a cultural-historical lens and a philological approach. Examining the legend’s diverse versions, the study reveals competing perceptions of Mary Magdalene’s body, highlighting its complex role in religious discourse. An appendix provides a comprehensive overview of the legend’s textual tradition.